Orígenes y su legado al Mundo Antiguo y al Mundo Moderno - Blázquez Martínez, José María (Gerión. Revista de Historia Antigua, 2010)
Today Origen is in fashion. He was very cultured and tried to transfer all his pagan ideas to the Christian World. This article studies the figure of Origen in the historians Eusebius of Caesarea, Socrates, Sozomen and Theodoret of Cyrrhus; in Epiphanius of Salamis, Theophilus and Jerome, the enemies of Origen. They are indicated the ideas that these authors rejected and the opinion from other Christian authors about them. This work depicts the opinions about Origen from Athanasius and Gregory Taumaturgus, mentions the principal followers of Origen. The influence of Origen in the Ancient World was very great. This article studies the position of Origen in the ancient pagan culture which was the assimilation of the contemporary thoughts, quite the contrary of the catholic hierarchy since Trento, that condemned up today the great creations of modernity; the ideas of the French Revolution, equality, fraternity, freedom, democracy, liberty of conscience and culture, separation of Church and State, human laws, the original Church preached it repeatingly very often. The article studies also the critical attitude of Origen about the State; the optimism of Origen; his posture about the Helenistic culture; about the jews and compare his positive attitude before the negative during centuries of the Roman christianity, that carries to the fossilization of the Christian thoughts. Origen was against the index of the forbidden books of Rome.
Keywords: Hellenism; Christianity; Partisan; Adversaries; Heresy; Model of Christianity; Sentence to Modernity; Defense of Ideas; Early Christianity; Fossilization of Christianity